2020
DOI: 10.1002/cbic.202000351
|View full text |Cite
|
Sign up to set email alerts
|

HaloTag‐Targeted Sirtuin‐Rearranging Ligand (SirReal) for the Development of Proteolysis‐Targeting Chimeras (PROTACs) against the Lysine Deacetylase Sirtuin 2 (Sirt2)**

Abstract: We have discovered the sirtuin-rearranging ligands (SirReals) as a novel class of highly potent and selective inhibitors of the NAD +-dependent lysine deacetylase sirtuin 2 (Sirt2). In previous studies, conjugation of a SirReal with a ligand for the E3 ubiquitin ligase cereblon to form a so-called proteolysistargeting chimera (PROTAC) enabled small-molecule-induced degradation of Sirt2. Herein, we report the structure-based development of a chloroalkylated SirReal that induces the degradation of Sirt2 mediated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…On the other hand, parkin E3 ligase exhibited moderate efficiency but showed broad responsiveness to all HaloPROTACs tested. Such HaloTag fusion proteins have also been utilized to develop Sirtuin-targeted PROTACs (termed SirReal, Figure 6 ) [ 92 ]. Quantitative analysis revealed distinct concentration-dependent effects on these HaloTag-E3 ligases of interest.…”
Section: Halotag-assisted Targeted Protein Modificationsmentioning
confidence: 99%
“…On the other hand, parkin E3 ligase exhibited moderate efficiency but showed broad responsiveness to all HaloPROTACs tested. Such HaloTag fusion proteins have also been utilized to develop Sirtuin-targeted PROTACs (termed SirReal, Figure 6 ) [ 92 ]. Quantitative analysis revealed distinct concentration-dependent effects on these HaloTag-E3 ligases of interest.…”
Section: Halotag-assisted Targeted Protein Modificationsmentioning
confidence: 99%
“…In 2018, a sirtuin rearrangement ligand (SirReals), as a highly potent and isoform-selective Sirt2 inhibitor conjugated to thalidomide, a bona fide cerebellar ligand, a PROTAC was developed to induce the degradation of Sirt2 in HeLa (Cervical cancer) cells and inhibit cell viability. On this basis, the team developed a PROTAC that used Parkin as an E3 ubiquitin ligase to target SIRT2 for degradation, providing a new direction for the development of PROTACs [ 88 , 89 ]. Subsequently, two PROTACs, TM-P2-Thal and TM-P4-Thal, were produced.…”
Section: Protacs For Epigenetic Targets In Cancermentioning
confidence: 99%
“…The results showed that PROTAC 54 can selectively and dose-dependently degrade sirt2 compared with Sirt2 inhibition. Subsequently, they designed and developed a Sirt2 degrader PROTAC 55 ( Table 2 ) [ 159 ] with a more optimized performance compared with PROTAC 54. PROTAC 55 can degrade Sirt2 at a 10-fold lower concentration than PROTAC 54.…”
Section: Application Of Protac In Immune Diseasesmentioning
confidence: 99%